History of Yugoslavia - Calic, Marie-Janine; Geyer, Dona; Project Muse. (West Lafayette, Indiana : Purdue University Press, 2019)
"Why did Yugoslavia fall apart? Was its violent demise inevitable? Did its population simply fall victim to the lure of nationalism? How did this multinational state survive for so long, and where do we situate the short life of Yugoslavia in the long history of Europe in the twentieth century? A History of Yugoslavia provides a concise, accessible, comprehensive synthesis of the political, cultural, social, and economic life of Yugoslavia--from its nineteenth-century South Slavic origins to the bloody demise of the multinational state of Yugoslavia in the 1990s. Calic takes a fresh and innovative look at the colorful, multifaceted, and complex history of Yugoslavia, emphasizing major social, economic, and intellectual changes from the turn of the twentieth century and the transition to modern industrialized mass society. She traces the origins of ethnic, religious, and cultural divisions, applying the latest social science approaches, and drawing on the breadth of recent state-of-the-art literature, to present a balanced interpretation of events that takes into account the differing perceptions and interests of the actors involved. Uniquely, Calic frames the history of Yugoslavia for readers as an essentially open-ended process, undertaken from a variety of different regional perspectives with varied composite agenda. She shuns traditional, deterministic explanations that notorious Balkan hatreds or any other kind of exceptionalism are to blame for Yugoslavia's demise, and along the way she highlights the agency of twentieth-century modern mass society in the politicization of differences. While analyzing nuanced political and social-economic processes, Calic describes the experiences and emotions of ordinary people in a vivid way."--Provided by publisher
1. The south Slavic countries around 1900 : the dawn of a new century -- 2. The national question across the Balkans (1875 to 1903) -- 3. Radicalization (1903 to 1912) -- 4. The three Balkan wars (1912/1913 to 1914/1918) -- 5. The Kingdom of Serbs, Croats, and Slovenes (1918 to 1929) -- 6. The 1920s : tradition and change -- 7. The Kingdom of Yugoslavia (1929 to 1941) -- 8. Occupation, collaboration, and resistance -- 9. The 1940s : total war -- 10. The consolidation of communist rule (1943 to 1948) -- 11. Tito's socialism (1948 to 1964) -- 12. The 1960s : transition to an industrial society -- 13. Reforms and rivalries (1964 to 1968) -- 14. The new nationalism (1967 to 1971) -- 15. After the boom years (1971 to 1980) -- 16. The crisis of socialist modernity (1980 to 1989) -- 17. The 1980s : anomie -- 18. Disintegration and the collapse of the state (1989 to 1991) -- 19. The War of Succession (1991 to 1999) -- 20. What remained of Yugoslavia -- Concluding remarks -- Appendix A: Parties, political organizations, and committees -- Appendix B: Maps -- Appendix C: Tables.
Description based on print version record.
Keywords: Yugoslavia; Yougoslavie -- Histoire -- 20e siecle; Yugoslavia -- History -- 20th century; HISTORY / Europe / Eastern; HISTORY -- Europe -- General; European history; History; Electronic books